Beyond The Dragon’s Magic: Eksplorasi Nilai Moral Anak dalam Film Wish Dragon: Beyond the Dragon’s Magic: Exploration of Children’s Moral Values in the Movie of Wish Dragon - Nurjannah, Alya (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
In the moden era, there have been various advancements in many aspects, one of which is technology. The rapid development of technology has provided convenience and somfort in people’s daily lives. However, such progress also brings new challenges, such as the decline of moral values in society, especially among children. Children now tend to use technology more as a form of entertainment, whish increases the importance of parental roles in guiding and supervising them. Technology plays a significant role in children’s development, including in supporting moral education. Since children are generally more attracted to visual entertainment, animated films serves as an effective medium for delivering moral messages. Children are not only entertained by engaging visuals but also able to understand the moral messages conveyed through the storyline. The researcher conducted an exploration of moral values in the animated film Wish Dragon, produced by Sony Pictures Animation. The film tells the story of a young boy and a magical dragon who attempts to fulfill his wish to reunite with his childhood friend. This study uses a descriptive qualitative method by analyzing dialogues and events in the film Wish Dragon. The results show that moral values can be implicity conveyed through the film’s intrinsic elements, such as charaters, plot, and setting.